2016
DOI: 10.1097/jnn.0000000000000219
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of Patients With Traumatic Brain Injury After Implementation of a Nurse Assessment Protocol

Abstract: Implementing the protocol, there was a reduction of death rate of patients with severe TBI and aftereffects in patients with moderate TBI. The severity of TBI was the main independent predictive determinant of mortality, followed by nonuse of protocol and age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Training using the best practice guidelines (Gocan & Fisher, ) or standardized neurological assessment tools (Iacono et al, ) were effective for improving nurses' competency level. Implementation of a nurse assessment protocol was also associated with better patient outcomes with reduced mortality (da P Oliveira et al, ). Patient simulation was also an effective educational strategy in improving nurses' self‐confidence (Garside et al, ; Mahaffey & Robertson, ) and self‐reported skills (Ross et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Training using the best practice guidelines (Gocan & Fisher, ) or standardized neurological assessment tools (Iacono et al, ) were effective for improving nurses' competency level. Implementation of a nurse assessment protocol was also associated with better patient outcomes with reduced mortality (da P Oliveira et al, ). Patient simulation was also an effective educational strategy in improving nurses' self‐confidence (Garside et al, ; Mahaffey & Robertson, ) and self‐reported skills (Ross et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Training approaches that have been found to be effective in improving nurses' performance of neurological assessment include lectures (Curley, ; Jones, ), e‐learning (Chiu et al, ; Shin, Issenberg, & Roh, ), hospital projects (da P Oliveira, Pereira, & da P Freitas, ; Gocan & Fisher, ; Iacono, Wells, & Mann‐Finnerty, ; Kirschen et al, ), and patient simulations (Garside, Rudd, & Price, ; Mahaffey & Robertson, ; Ross et al, ). The analysis of training needs provides the basis for continuing professional development (Holloway, Arcus, & Orsborn, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nursing assessments in the acute care setting are the foundation for immediate interventions and serve as the pathway for the patient to advance through the phases of care, which emphasizes continuity of evaluation and adaptability. By implementing protocols designed for the treatment of patient with traumatic brain injuries, there has shown to be a reduction in the death rate of patients with severe TBI and decreased aftereffects in patients with moderate TBI [3].…”
Section: Introductionmentioning
confidence: 99%